MiRNome of Italian Large White pig subcutaneous fat tissue: new miRNAs, isomiRs and moRNAs. (16th July 2014) - Gaffo, Enrico; Zambonelli, Paolo; Bisognin, Andrea; Bortoluzzi, Stefania; Davoli, Roberta
Summary Small RNAs, such as micro‐RNAs (miRNAs), are decisive regulators of gene expression, and they could determine adipose tissue traits. A better knowledge of porcine fat genomics is relevant given that the pig is a biomedical model for metabolic and cardiovascular human pathologies. Adipose tissue is particularly important for the meat industry. We explored the miRNome of two adult Italian Large White pig backfat samples by Illumina RNA‐Seq. Using custom bioinformatic methods, the expressed miRNAs were identified and quantified and the nucleotide sequence variability of miRNA isoforms were analysed. We detected 222 known miRNAs, 68 new miRNAs and 17 miRNA‐offset RNAs (moRNAs) expressed from known hairpins, and 312 new miRNAs expressed from 253 new hairpins. Porcine transcripts targeted by the most expressed miRNAs were predicted, showing that these miRNAs may have an impact on Wnt, insulin signalling and axon guidance pathways. The expression of five small RNAs, including moRNA ssc‐5′‐moR‐21 and a miRNA from a new hairpin, was validated by a qRT‐PCR assay, thus confirming the robustness of our results. The depicted miRNome complexity suggests that quantitative and qualitative features of miRNAs and non‐canonical products of their precursors are worthy of further investigation to clarify their roles in the adipose tissue biology.